Competition and loan portfolio quality in the Peruvian microfinance market, 2003-2015 - Mayorca Huamán, Ellen (2016)
The aim of this study is to analyze the relationship between competition and loan portfolio quality in the Peruvian microfinance sector. To make this analysis the market is segmented into three groups of microfinance microfinance institutions IMFs), considering the average volume of its loans. So that, in the first group (large IMFs) entities of higher average volume of loans are located, in the second group (medium IMFs) entities with an average volume of loans are located and finally, in the third group (small IMFs) are entities with lower average loan volumes.This segmentation reflects the heterogeneity of size for loans between IMFs. The results show the Lerner index decreasing over time, for both the group of large IMFs and the group of small IMFs, showing a decrease of market power and increased competition in these two groups of entities. In the group of medium IMFs behavior Lerner index shows a growing trend in the last months of the period studied thus indicating a greater market power and less competition in this group of microfinance operators. On the other hand, an inverse relationship between the Lerner index over delinquency rate in the three groups of IMFs is found, implying that increased competition in the Peruvian microfinance market has deteriorated the quality of loan portfolio the period analyzed. This result is obtained by controlling the behavior of other important variables to explain the delinquency rate such as the business cycle, credit expansion, efficiency and profitability of institutions, and the effect of the international financial crisis of 2008.